(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2015)
This article deals with the gem engraver (Maria) Teresa Talani, acting in the last decade of the 18th - first quarter of the 19th centuries. In her time she was appreciated and famous, but now is little known. The original carvings by Talani that still survive and are published are quite few; here a catalogue of her cameos and intaglios is proposed. Moreover, in the present study are published some very interesting documents, that give fundamental information for a clearer understanding of Talani’s figure and to resolve complicated matters concerning such artist. Teresa Talani was born not in Rome, as many scholars assert, but in Bergamo, perhaps daughter of Giovanni Moro / Moor, gem engraver living in Venice. Teresa Talani was wife of Vincenzo Talani, an art dealer with several links to Neapolitan court; they stayed in Naples for a long time. In the age of Napoleon the artist moved to Milan, working for powerful and prestigious patrons, such as the Napoleonic court and the Count Giovanni Battista Sommariva.